Centrifugal Spinning Enables the Formation of Silver Microfibers with Nanostructures - Xujing Zhang; Songsong Tang; Zhaokun Wu; Ye Chen; Zhen Li; Zongqian Wang; Jian Zhou (Nanomaterials, 2022)
Silver nanowires (AgNWs) have received much attention and application in transparent electrodes, wearable electronic devices, and sensors. The hope is for these nanowires to eventually replace the most commonly used transparent electrode material—indium tin oxide (ITO). However, electrospinning used for the preparation of AgNWs on a large scale is limited by its low productivity and high electric field, while the alcohol-thermal method is limited to mixing by-product silver nanoparticles in silver nanowires. We demonstrate a novel and simple centrifugal spinning approach in order to successfully fabricate ultra-long silver microfibers based on AgNO3 and polyvinyl pyrrolidone (PVP). The centrifugal-spun precursor fiber and silver fiber can be prepared to as thin as 390 and 310 nm, respectively. Annealed fibers show typical nanostructures with grains down to a minimum size of 51 nm. Combinations of different parameters, including concentrations of PVP, needle size, and annealing temperature are also investigated, in order to optimize the spinning process of ultra-long silver microfibers. The feasibility of preparing silver microfibers by centrifugal spinning is preliminarily verified, examining prospects for mass production. Furthermore, numerous strategies related to assisting the creation of silver nanofibers using centrifugal spinning are presented as possibilities in future development.